2007
DOI: 10.1111/j.1467-839x.2007.00234.x
|View full text |Cite
|
Sign up to set email alerts
|

On helping lower status out‐groups: The nature of the help and the stability of the intergroup status hierarchy

Abstract: The current research expanded upon previous theoretical and empirical arguments regarding the nature of intergroup helping. In doing so, we considered the role of relative in-group status, the stability of this status, and the type of help provided. In a scenario study, we observed that members of a relatively high status group more strongly supported the provision of assistance to in-group members than members of a lower status out-group when the assistance was empowering in nature and when the high in-group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
30
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 26 publications
4
30
1
Order By: Relevance
“…Whether it is financial assistance or specific expertise, the receipt of help can improve the helpee's situation. Help is useful in promoting learning (A. M. Ryan & Pintrich, 1997) and in removing barriers that interfere with the ability to achieve important goals (Cunningham & Platow, 2007;Jackson & Esses, 2000). In organizational contexts, the importance of seeking help has long been recognized as an important part of organizational learning (Ashford & Cummings, 1985;Morrison, 2002;Rashman, Withers, & Hartley, 2009;Schilling & Kluge, 2009).…”
mentioning
confidence: 99%
“…Whether it is financial assistance or specific expertise, the receipt of help can improve the helpee's situation. Help is useful in promoting learning (A. M. Ryan & Pintrich, 1997) and in removing barriers that interfere with the ability to achieve important goals (Cunningham & Platow, 2007;Jackson & Esses, 2000). In organizational contexts, the importance of seeking help has long been recognized as an important part of organizational learning (Ashford & Cummings, 1985;Morrison, 2002;Rashman, Withers, & Hartley, 2009;Schilling & Kluge, 2009).…”
mentioning
confidence: 99%
“…Together, the existing literature suggests that perceived threats -including perceptions that one's values are being violated, economic competition, group status instability, and harmful actions to public health -reduce prosocial behavior toward the target out-group (Cunningham & Platow, 2007;Flippen, et al, 1996;Jackson & Esses, 1997. Therefore, we expect that intergroup threat not only increases negative intergroup attitudes and behavior, but also decreases positive intergroup behavior, specifically, out-group helping.…”
Section: Introductionmentioning
confidence: 99%
“…In the present research, the manipulation of intergroup threat concerns a history of warfare between national groups, since evidence has shown that groups with a long history of conflict are the most prone to perceive realistic intergroup threat (Shamir & Sagiv-Schifter, 2006;. unemployment problems) (Cunningham & Platow, 2007;Jackson & Esses, 1997. In the present research, the helping context concerns a natural disaster.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations